OPTIMALISASI MOTIVASI KERJA DOSEN DALAM PENINGKATAN KUALITAS PENGAJARAN DI PERGURUAN TINGGI: KAJIAN LITERATUR - Siti, Fatimatus Syarifah; Adilatus, Shofiyah; Holilatus, Sahdiyah; Amalia, Wanda Mega Retha; Abdul, Khusi Mubarok; Mu’alimin (JOURNAL J-MPI : JURNAL MANAJEMEN PENDIDIKAN, PENELITIAN DAN KAJIAN KEISLAMAN, 2025)
The success of the learning process, students' academic growth, and the standing of educational institutions are all significantly impacted by lecturers' dedication to raising the standard of instruction. The purpose of this study is to examine how lecturers use work motivation techniques to enhance the caliber of their instruction. This study's methodology is qualitative and involves a literature review or library research strategy. Data is gathered by looking through a variety of scholarly sources, including books, journals, and pertinent prior research. This study's primary goal is to determine the elements that affect lecturers' motivation for their jobs and assess how well the strategies employed to address these issues function. Based on the study's findings, lecturers' motivation for their jobs is affected by a number of internal, external, and organizational elements. As a result, this study helps create better strategies to raise the professionalism of lecturers